2018 IEEE/OES Autonomous Underwater Vehicle Workshop (AUV) 2018
DOI: 10.1109/auv.2018.8729718
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Cold-Water Corals in Synthetic Aperture Sonar Imagery

Abstract: The deep-water coral Lophelia pertusa is a common reef-building scleractinian coral, or stony coral, occurring in mid to deep waters around the world. The reefs they form are regarded as hot spots for biodiversity and carbon cycling, and play a key role in benthic ecosystems in Norwegian waters. The cold-water reefs are however under increasing anthropogenic pressure due to human activities and a changing environment. Development of methods that enable time-and cost-effective monitoring of these reefs is there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…To record sonar imagery, a Kongsberg HiSAS 1030 synthetic aperture sonar system (Kongsberg Maritime AS, Kongsberg, Norway) was deployed on a HUGIN 1000 AUV. As opposed to regular side-scanning sonar systems, SAS systems utilize more than a single ping to reconstruct a given location in the output imagery, which improves spatial resolution both across-and along-track (Hansen et al, 2004;Sture et al, 2018). Using the SASequipped HUGIN AUV, the northwestern region of the Tautra Ridge was surveyed in a systematic lawnmower pattern at a mean seafloor altitude of 26 m. The resulting imagery was postprocessed in Kongsberg Maritime's "Reflection" software, and ultimately georeferenced at a pixel resolution of 4 cm x 4 cm.…”
Section: Sas Datamentioning
confidence: 99%
See 2 more Smart Citations
“…To record sonar imagery, a Kongsberg HiSAS 1030 synthetic aperture sonar system (Kongsberg Maritime AS, Kongsberg, Norway) was deployed on a HUGIN 1000 AUV. As opposed to regular side-scanning sonar systems, SAS systems utilize more than a single ping to reconstruct a given location in the output imagery, which improves spatial resolution both across-and along-track (Hansen et al, 2004;Sture et al, 2018). Using the SASequipped HUGIN AUV, the northwestern region of the Tautra Ridge was surveyed in a systematic lawnmower pattern at a mean seafloor altitude of 26 m. The resulting imagery was postprocessed in Kongsberg Maritime's "Reflection" software, and ultimately georeferenced at a pixel resolution of 4 cm x 4 cm.…”
Section: Sas Datamentioning
confidence: 99%
“…The HUGIN AUV was equipped with a synthetic aperture sonar (SAS), and the recorded sonar imagery clearly revealed the presence of cauliflower-patterned reef structures (Ludvigsen et al, 2014). Sture et al (2018) later demonstrated that these D. pertusum reefs could be accurately identified in SAS imagery by applying a convolutional neural network (CNN) classification algorithm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, for the deep-sea, passive hyperspectral remote sensing is no longer applicable. Current methods at disposal for obtaining descriptions of seafloor benthic habitats and organisms are sonar surveying, underwater photography, and grab or trawl sampling [ 78 , 79 , 80 ]. Sonar surveying is more concerned with the topographical features of benthic habitats.…”
Section: Applications Of Underwater Hyperspectral Imaging Technolomentioning
confidence: 99%
“…A variety of algorithms exist for forming images from SAS acoustic measurements [3]- [6]. These reconstruction algorithms aim to produce high quality imagery to support underwater visualization tasks including target localization [7], monitoring man-made infrastructure [8], and studying underwater ecologies [9].…”
Section: Introductionmentioning
confidence: 99%